Consensus of networked control multi-agent systems using a double-layer encryption scheme - Yamin Yan; Zhiyong Chen; Vijay Varadharajan (Journal of Automation and Intelligence)
This paper addresses the decentralized consensus problem for a system of multiple dynamic agents with remote controllers via networking, known as a networked control multi-agent system (NCMAS). It presents a challenging scenario where partial dynamic entities or remote control units are vulnerable to disclosure attacks, making them potentially malicious. To tackle this issue, we propose a secure decentralized control design approach employing a double-layer cryptographic strategy. This approach not only ensures that the input and output information of the benign entities remains protected from the malicious entities but also practically achieves consensus performance. The paper provides an explicit design, supported by theoretical proof and numerical verification, covering stability, steady-state error, and the prevention of computation overflow or underflow.